Возможности использования каналов низкого качества в многоконтурных системах с решающей обратной связью - Логвиненко, Н. Ф.; Серков, О. А. (Проблеми телекомунікацій, 2010)
Systems with decision feedback with two and three feedback loops are compared on the criterion of the average relative speed of data to compare. At the same time on the last loop-interference block (n,k)-the code is used in mode of the finding error. For a two-contour system on the ground, and for three-contour system on the first and second contour used corrective Hamming codes.
Keywords: решающая обратная связь; передача данных; помехоустойчивые блочные коды; исправление ошибок; кратные ошибки